(untitled) (Research, Society and Development, 2021)
Objective: to identify the occurrence of stress, and sociodemographic vulnerabilities, in undergraduate nursing students. Methodology: This is a quantitative, cross-sectional, epidemiological study, with 59 undergraduate students in Nursing in the city in the central-west of the state of São Paulo. Data were collected between the months of September and October 2018, using a semi-structured questionnaire, prepared by the authors and the Perceived Stress Scale. The data were analyzed with descriptive statistics and inferential analysis with one-way ANOVA and two-factor ANOVA, with the stress score obtained using the Perceived Stress Scale as the dependent variable, and sociodemographic variables as predictors. The Levene Equality of Variance Test was carried out and there was no statistically significant difference between all the variables in this study. The level of significance adopted for the analyzes of this study was p <0.05. Results: This study obtained the voluntary participation of 59 (48.0%) undergraduate nursing students, of 123 (100.0%) possible, who had a general average of scores on the Perceived Stress Scale equal to 28.2 and fashion 27.0. There was a statistically significant difference between the stress tracking by the score obtained in the application of the Perceived Stress Scale in university students with mental disorder (p = 0.020), so that it is possible to state that students diagnosed with mental disorders have a higher level of stress when compared to university students who are not diagnosed with mental disorders. Final considerations: Considering that all variables had a p-value greater than 0.05, the null hypothesis is accepted, so that there is no interaction between the fact of working and the variables studied that result in a different perception of stress.